Brain regions associated with the acquisition of conditioned place preference for cocaine vs. social interaction - El Rawas, Rana; Klement, Sabine; Kummer, Kai; Fritz, Michael; Dechant, Georg; Saria, Alois; Zernig, Gerald (Frontiers in Behavioral Neuroscience, 2012)
Positive social interaction could play an essential role in switching the preference of the substance dependent individual away from drug related activities. We have previously shown that conditioned place preference (CPP) for cocaine at the dose of 15 mg/kg and CPP for four 15-min episodes of social interaction were equally strong when rats were concurrently conditioned for place preference by pairing cocaine with one compartment and social interaction with the other. The aim of the present study was to investigate the differential activation of brain regions related to the reward circuitry after acquisition/expression of cocaine CPP or social interaction CPP. Our findings indicate that cocaine CPP and social interaction CPP activated almost the same brain regions. However, the granular insular cortex and the dorsal part of the agranular insular cortex were more activated after cocaine CPP, whereas the prelimbic cortex and the core subregion of the nucleus accumbens were more activated after social interaction CPP. These results suggest that the insular cortex appears to be potently activated after drug conditioning learning while activation of the prelimbic cortex - nucleus accumbens core projection seems to be preferentially involved in the conditioning to non-drug stimuli such as social interaction.